2022
DOI: 10.1242/jcs.258644
|View full text |Cite
|
Sign up to set email alerts
|

HDLs extract lipophilic drugs from cells

Abstract: High-density lipoproteins (HDLs) prevent cell death induced by a variety of cytotoxic drugs. The underlying mechanisms are however still poorly understood. Here we present evidence that HDLs efficiently protect cells against thapsigargin (TG), a sarco/ endoplasmic reticulum (ER) Ca2+-ATPase (SERCA) inhibitor, by extracting the drug from cells. Drug efflux could also be triggered to some extent by low-density lipoproteins and serum. HDLs did not reverse the non-lethal mild ER stress response induced by low TG c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The specific primers are as follows: ATF3, forward: 5′‐TAG CCC CTG AAG AAG ATG AAA G‐3′ and reverse: 5′‐CTT CTT CTT GTT TCG GCA CTT T‐3′; ATF4, forward: 5′‐ATG GAT TTG AAG GAG TTC GAC T‐3′ and reverse: 5′‐AGA GAT CAC AAG TGT CAT CCA A‐3′; ATF6, forward: 5′‐CTG ATG GCT GTT CAA TAC ACA G‐3′ and reverse: 5′‐GAT CCC TTC GAA ATG ACA CAA C‐3′. The primers of BIP, CHOP and GAPDH used in this study were described previously 28–30 . GAPDH served as control to normalize mRNA expression level.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific primers are as follows: ATF3, forward: 5′‐TAG CCC CTG AAG AAG ATG AAA G‐3′ and reverse: 5′‐CTT CTT CTT GTT TCG GCA CTT T‐3′; ATF4, forward: 5′‐ATG GAT TTG AAG GAG TTC GAC T‐3′ and reverse: 5′‐AGA GAT CAC AAG TGT CAT CCA A‐3′; ATF6, forward: 5′‐CTG ATG GCT GTT CAA TAC ACA G‐3′ and reverse: 5′‐GAT CCC TTC GAA ATG ACA CAA C‐3′. The primers of BIP, CHOP and GAPDH used in this study were described previously 28–30 . GAPDH served as control to normalize mRNA expression level.…”
Section: Methodsmentioning
confidence: 99%
“…The primers of BIP, CHOP and GAPDH used in this study were described previously. 28 , 29 , 30 GAPDH served as control to normalize mRNA expression level.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, the lipoprotein-mediated drug transport is a potential contributor to the transport and metabolism of lipophilic drugs in the body, the role of which should be considered when developing new pharmacotherapies [24]. In line with this, the evidence of the lipoprotein transport of fat-soluble xenobiotics would mean that lipoproteins are involved in the distribution and toxic effects of these chemicals in the body [26].…”
Section: Transport Of Lipophilic Substances Other Than Plasma Lipidsmentioning
confidence: 98%
“…A recent study showed that HDLs can utilize their capacity of loading themselves with lipophilic compounds, similarly to their ability to extract cellular cholesterol, to reduce the cell content of lipophilic drugs and xenobiotics. ABC transporters were not required for the process, but however, could favor it [26].…”
Section: Experimental Evidence Of the Role Of Hdlmentioning
confidence: 99%